(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe factors related to the knowledge and practice of elderly people with type 2 diabetes about insulin injection at the National Geriatric Hospital in 2023. Subject and method: A cross-sectional study was performed on 250 elderly patients (over 60 years old) diagnosed with type 2 diabetes and treated at the National Hospital of Geriatrics. We used the reference tool set from the ITQ-2015 scale to assess the level of knowledge and practice of selfinjection of Insulin. Results: Patients who used syringes or both syringe and injection pen (OR=3,34; 95%CI: 1,45- 7,73), were injected insulin more than once a day (OR=2,26; 95%CI: 1,09-4,70), and were consulted by medical staff for the past 6 months gained higher knowledge than the rest group (OR=3,50; 95%CI: 1,59-7,69). The level of achieving insulin injection practice was higher in the group of elderly people with higher education (OR=1,97; 95%CI: 1,11-3,51) and having history of diabetes complications(OR=2,11; 95%CI: 1,19-3,73); use a syringe/both syringe and injection pen (OR=2,63; 95%CI: 1,17-5,87); received the instructions from both nurses and doctors in terms of insulin injection (OR=2,15; 95%CI: 1,22-3,80); and patients with good knowledge (OR=3,37; 95%CI: 1,74-6,52). Conclusion: The knowledge and practice of insulin injection among the elderly in the National Geriatric Hospital are low. Factors related to the knowledge and practice of the elderly include: Education level, diabetes complications, insulin injection equipment, insulin injection instruction subjects, knowledge of insulin injection and history of diabetes complications. To improve the knowledge and practice of the elderly, it is necessary to strengthen counseling, education, knowledge and practice of Insulin injection for elderly patients.